2015
DOI: 10.1002/polb.23716
|View full text |Cite
|
Sign up to set email alerts
|

The linear rheological responses of wedge‐type polymers

Abstract: The linear rheological responses of a series of specially designed wedge-type polymers synthesized by the polymerization of large molecular weight monomers have been measured. These wedge polymers contained large side groups which contained three flexible branch chains per polymer chain unit. The master curves for these polymers were obtained by time temperature superposition of dynamic data at different temperatures from the terminal flow regime to well below the glass transition temperature, T g . While thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
34
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 62 publications
7
34
0
Order By: Relevance
“…Several studies investigated the zero shear viscosity η 0 as a function of total molecular weight for different series of loose and dense bottlebrushes with either short chain branches (SCB) [13,18,19,24,[29][30][31]57] or long chain branches (LCB). [11,30] Within these bottlebrush series, two characteristics out of n sc , n g , and n bb are fixed and one of them is varied in the series.…”
Section: Zero Shear Viscositymentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies investigated the zero shear viscosity η 0 as a function of total molecular weight for different series of loose and dense bottlebrushes with either short chain branches (SCB) [13,18,19,24,[29][30][31]57] or long chain branches (LCB). [11,30] Within these bottlebrush series, two characteristics out of n sc , n g , and n bb are fixed and one of them is varied in the series.…”
Section: Zero Shear Viscositymentioning
confidence: 99%
“…[58] It can be seen in Figure 5b that the Rouse and reptation relaxation mechanisms have a sharp transition at M w /M e = 1. Grubbs and co-workers [13] showed that the scaling exponent of the zero shear viscosity-molecular weight dependence of a series of entangled wedge polymers (very dense bottlebrushes with three branches per repeating unit of backbone, i.e., n g ≈ 0.3) with SCB structure might be even above the 3 power law with an exponent of around 4.2. The main difference between the linear and SCBbottlebrushes is related to the friction coefficient, where in the linear polymers is due to the monomers on the backbone but in SCB-bottlebrushes is caused by monomers on the surface of the bottlebrush cylinders.…”
Section: Zero Shear Viscositymentioning
confidence: 99%
See 2 more Smart Citations
“…ROMP can produce polymers with large MWs and extremely narrow molecular weight distributions ( Đ ) and is used to synthesize polymers with unique characteristics. ROMP is compatible with sophisticated monomers such as macromonomers which form bottle‐brush polymers and dendritic wedge‐like monomers which form polywedges . These polymers are designed to have very high critical molecular weights and avoid chain entanglement.…”
Section: Introductionmentioning
confidence: 99%